Smoking recurrence: A Survival Analysis - Ana Beatriz Ramos da Silva; Débora de Sousa Cordeiro; Giovana de Souza (Socioeconomic Analytics)
This study applies Survival Analysis to model the time until smoking relapse, considering social, demographic and clinical variables, such as age group, gender, type of treatment and time as a smoker. Survival curves are estimated using the Kaplan-Meier and Nelson-Aalen methods, showing differences between groups. The Logrank and Wilcoxon tests indicated significance only for age group. In the Cox modeling, the type of treatment and age group stood out as relevant. It was concluded that combined treatments with three interventions are more effective, especially for young people, who require greater support and awareness.